1999
DOI: 10.2323/jgam.45.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of triacylglycerol-secreting mutant strain from yeast, Saccharomyces cerevisiae.

Abstract: In recent times, demands for bio-oils, such as biolipids and biofuels, have progressed, since they are very significant biomolecules for human health and for the ecological preservation of the earth's environment. Nevertheless, the supplements of bio-oils were not always stable because the harvests of oleaginous plants, animals, and fishes were influenced by climates and marine conditions. Various research and developments were carried out on microbial production of valuable oils, such as polyunsaturated fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…These genes were identified to have a function in fatty acid secretion through the use of a screening method wherein mutated yeast colonies were overlaid with an agar containing a fatty acid auxotrophic yeast strain that requires free fatty acids in order to proliferate. Mutant colonies that secrete fatty acids were thereby identified by the formation of a halo in the overlaid agar (120,132). Similar screening methods could be utilized to identify mi-croalgae that have the ability to secrete fatty acids.…”
Section: Secretion Of Triacylglycerol Alkanes Free Fatty Acids Andmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes were identified to have a function in fatty acid secretion through the use of a screening method wherein mutated yeast colonies were overlaid with an agar containing a fatty acid auxotrophic yeast strain that requires free fatty acids in order to proliferate. Mutant colonies that secrete fatty acids were thereby identified by the formation of a halo in the overlaid agar (120,132). Similar screening methods could be utilized to identify mi-croalgae that have the ability to secrete fatty acids.…”
Section: Secretion Of Triacylglycerol Alkanes Free Fatty Acids Andmentioning
confidence: 99%
“…In one of the yeast studies, random mutagenesis resulted in the secretion of TAGs. Unfortunately, neither the genes involved nor the mechanism has been described (132). S. cerevisiae has five genes with fatty acyl-CoA synthetase activity, including those encoding FAA1 and FAA4.…”
Section: Secretion Of Triacylglycerol Alkanes Free Fatty Acids Andmentioning
confidence: 99%
See 1 more Smart Citation
“…the biomass arouses interest in regard to its lipid content, since microbial lipids are related to the structural and protective role of cell membranes of microrganisms. lipid characterization of yeasts and preparation of lipids as biologically active products have been studied by a large number of researchers (10,13,19). the lipid composition determines the physical properties of the membranes and changes according to the thermal habitat of microorganisms.…”
Section: Antarctic Yeasts From Genus Sporobolomyces and Genusmentioning
confidence: 99%
“…69 It is found that knocking out genes involved in β-oxidation not only can lead to increased amounts of intracellular free fatty acids but also result in extracellular fatty acid secretion in some cases. [70][71][72] For example, deletion of the fadD gene (encoding the fatty acyl-CoA synthetase) in E. coli could result in an enhanced fatty acids accumulation. 32 The same positive effect on the fatty acids accumulation achieved by knocking out of the fadE gene coding acyl-CoA dehydrogenase in E. coli.…”
Section: Genetic Engineering In Fatty Acids Pathwaymentioning
confidence: 99%